Tazarotene induces apoptosis in human basal cell carcinoma via activation of caspase-8/t-Bid and the reactive oxygen species-dependent mitochondrial pathway - Wu, Chieh-Shan; Chen, Gwo-Shing; Lin, Ping-Yi; Pan, I-Hong; Wang, San-Tang; Lin, Sheng Hao; Yu, Hsin-Su; Lin, Chi-Chen (DNA and cell biology, 2014)
Previous studies suggest that tazarotene, a new member of the acetylenic class of RARβ/γ selective retinoids which is approved to treat a variety of skin diseases, exhibits an anti-proliferative effect in human basal cell carcinoma (BCC) by triggering caspase-dependent apoptosis. However, the detailed molecular mechanisms underlying the anti-tumor activity of tazarotene are poorly understood. This study aims at investigating the molecular mechanisms of tazarotene-induced apoptosis in human BCC cells. Our results are the first to demonstrate that tazarotene induces mitochondria-dependent cleavage of caspase-9 and -3 and PARP in BCC cells by producing reactive oxygen species (ROS) and activating caspase-8 through both ROS and death receptor signaling. These events are accompanied by a decrease in BCL-2 and BCL-xl anti-apoptotic proteins as well as by survivin and XIAP, two IAP family members. Furthermore, our results presented for the first time that tazarotene triggers a convergence of the intrinsic and extrinsic apoptotic pathways via the caspase-8-truncated Bid signaling pathway. Collectively, these data provide insights into the molecular mechanisms underlying tazarotene-induced apoptosis in human BCC cells, suggesting that this compound is a potential anti-skin cancer drug.